Consumer perceived value and impulse buying behavior on mobile commerce: The moderating effect of social influence. (November 2021) - Yang, Feng; Tang, Jing; Men, Jinqi; Zheng, Xiabing
Abstract: This study examines how the consumers' perceived values (utilitarian and hedonic values) impact their impulse buying behavior (IBB) in the mobile commerce (m-commerce) context. Moreover, we view interpersonal influence as a moderator and test its impact on the correlation between the consumers' perceived value and their IBB. Data were collected through a survey in China (n = 199). The results show that environmental stimuli significantly influence consumer perceived values (i.e., perceived utilitarian value and perceived hedonic value), and the consumers' perception of hedonic value significantly and directly impacts their IBB. In addition, the interaction effect of perceived hedonic value and interpersonal influence significantly affects IBB. The findings provide valuable guidance for m-commerce retailers to induce consumer IBB. Graphical abstract: This study examines how the consumers' perceived values (perceived utilitarian and hedonic values) impact their impulse buying behavior in the m-commerce context. Moreover, we view interpersonal influence as a moderator variable and test its moderating effect on the relationship between the consumers' perceived value and their impulse buying behavior. Image 1